Growth of anatase titanium dioxide nanotubes via anodization - Dilla, Ed Adrian (Science Diliman, 2012)
In this work, titanium dioxide nanotubes were grown via anodization of sputtered titanium thin films using different anodization parameters in order to formulate a method of producing long anatase titanium dioxide nanotubes intended for solar cell applications. The morphological features of the nanotubes grown via anodization were explored using a Philips XL30 Field Emission Scanning Electron Microscope. Furthermore, the grown nanotubes were also subjected to X-ray diffraction and Raman spectroscopy in order to investigate the effect of the predominant crystal orientation of the parent titanium thin film on the crystal phase of the nanotubes. After optimizing the anodization parameters, nanotubes with anatase TiO2 crystal phase and tube length more than 2 microns was produced from parent titanium thin films with predominant Ti(010) crystal orientation and using ammonium fluoride in ethylene glycol as an electrolyte with a working voltage equal to 60V during 1-hour anodization runs. [ABSTRACT FROM AUTHOR]